2010
DOI: 10.1089/fpd.2009.0374
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisDetection in Individual and Bulk Tank Milk Samples from Bovine Herds and Caprine Flocks

Abstract: Paratuberculosis, or Johne's disease, is caused by Mycobacterium avium subsp. paratuberculosis (Map), and it generates great economic losses for the dairy industry worldwide. In humans, Map has been associated with Crohn's disease. Mexico has unknown paratuberculosis prevalence, and yet, control programs have not been applied. This study aimed to determine the presence of Map in milk samples from seropositive goats and cows and bulk tank milk samples from herds previously designated Map-infected using indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…People are exposed to MAP by direct contact with infected material and in retail milk supplies [17]. Ruminant milk has been described as a potential source through which human beings could be infected [18, 19]. Viable MAP has been isolated from milk and colostrum of clinically and subclinically infected cows [20], and infection of the mammary gland has been documented in small ruminants [21].…”
Section: Introductionmentioning
confidence: 99%
“…People are exposed to MAP by direct contact with infected material and in retail milk supplies [17]. Ruminant milk has been described as a potential source through which human beings could be infected [18, 19]. Viable MAP has been isolated from milk and colostrum of clinically and subclinically infected cows [20], and infection of the mammary gland has been documented in small ruminants [21].…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to other recent estimates of herd-level MAP prevalence in other countries. For instance, ELISA studies of BTM samples collected in Spain showed that 9.2% of the samples were positive (Boadella et al, 2010), while studies in Mexico that employed indirect ELISAs found that MAP prevalence ranged between 8.0% and 24.07% in the dairy herds and 8.29% and 9.67% in the caprine flocks examined in the study (Favila-Humara et al, 2010). Sero-prevalence of MAP has been detected in dairy cattle throughout South Korea (Lee and Jung, 2009;Park et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…However, in other studies in which ELISA was used, the seroprevalence was higher (Fávila et al, 2009(Fávila et al, , 2010Toledo et al, 2010;Gallaga et al, 2017).…”
Section: Discussionmentioning
confidence: 83%